2022
DOI: 10.1039/d2ra03417d
|View full text |Cite
|
Sign up to set email alerts
|

Facile production of chitin from shrimp shells using a deep eutectic solvent and acetic acid

Abstract: High purity chitin was extracted from shrimp shells by a green, sustainable, and efficient one-pot approach using a deep eutectic solvent consisting of choline chloride and glycerol (ChCl–Gl) combined with a small amount of acetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The viscosity-average molecular weight ( M v ) of samples was measured by dissolving 9 mg of sample in 30 mL of 5 wt% LiCl in N , N -dimethylacetamide (DMAc). 35,36 The mixture of chitinous sample and solvent was stirred for two days at room temperature, and then the intrinsic viscosity [ η ] of the solution was measured on a Brookfield DV-II Pro Viscometer (Bruchsal, Germany) at 25 °C. The obtained viscosity was applied to the Mark–Houwink-Sakurada equation to calculate M v .[ η ] = KM α V where α = 0.95 and K = 0.0076 mL g −1 are constants for the solution prepared in 5 wt% LiCl/DMAc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity-average molecular weight ( M v ) of samples was measured by dissolving 9 mg of sample in 30 mL of 5 wt% LiCl in N , N -dimethylacetamide (DMAc). 35,36 The mixture of chitinous sample and solvent was stirred for two days at room temperature, and then the intrinsic viscosity [ η ] of the solution was measured on a Brookfield DV-II Pro Viscometer (Bruchsal, Germany) at 25 °C. The obtained viscosity was applied to the Mark–Houwink-Sakurada equation to calculate M v .[ η ] = KM α V where α = 0.95 and K = 0.0076 mL g −1 are constants for the solution prepared in 5 wt% LiCl/DMAc.…”
Section: Methodsmentioning
confidence: 99%
“…The results of viscosity-average molecular weight showed that chitin has a M v of 215.6 kDa, which is comparable with the M v of chitin derived from shrimp shells as reported in the literature. 35 FC has an M v of 89.5 kDa, indicating the depolymeriza-tion of chitin during formic acid treatment. The decrease in the degree of polymerization of the substrate could also contribute to the conversion into HMF.…”
Section: Physicochemical Properties Of Samplesmentioning
confidence: 99%
“…Recently, [Cho]Cl/Glycerine (1:2 mol/mol) was proposed to separate chitin from shrimp shell powder using ball-milling. After ball-milling the DES and shrimp shell for 3 h at 100 °C, acetic acid was added, resulting in a 25.8% yield after discoloration ( Table 1 , entries #6–12) [ 57 ]. When the acetic acid concentration was raised from 2.5 to 10.0 wt%, the chitin yields decreased gradually from 28.5 to 21.0%.…”
Section: Chitin Isolation From Biomass-waste With Dessmentioning
confidence: 99%
“…Acetic acid is the most widely used aliphatic carbonic acid. It is frequently used as a solvent in the manufacture of cellulose acetate and many pharmaceutical products [28][29][30][31]. The use of acetic acid in plants is also beneficial for improving drought tolerance and reducing growth inhibition in agricultural fields [32].…”
Section: Introductionmentioning
confidence: 99%